Sistematización de los formularios médico ocupacionales del ministerio de salud pública para el departamento médico ocupacional de la Universidad Técnica De Cotopaxi - Chávez Chávez, Milton Alfredo (2020)
This paper presents the process of implementing a web application for the management of medical forms in the Occupational Medical Department (OMD) of the Technical University of Cotopaxi. The forms are provided by the Ministry of Public Health of Ecuador and they were originally handled through spreadsheets in the Excel tool; through this system whose objective is to systematize the forms and above all to automate the issuance of medical certificates and individual reports per patient, an analysis work was carried out with the medical professional responsible for the OMD, Dr. Richard Pérez, who provided the entire knowledge base so that the system, through a set of formulas that analyzes the information entered in the medical records, generates the diagnosis of aptitude and occupational risk of the patients. The goal set has been achieved; the web application, due to security issues, will work locally in the institution's OMD, which has gone through a rigorous validation process, which is why it has the implementation endorsement given by the direct end user